THE MODEL OF COMPETENCY DEVELOPMENT FOR TELEVISION NEWS BROADCASTERS IN THAILAND - Phatthanachirarut, Ratthawat; Taesilpasatit, Anupong (Journal of Buddhist Anthropology, 2022)
The objectives of this research article were to 1) study operating conditions, problems and current obstacles of television news broadcasters for television broadcasting in Thailand, 2) study the competence of television news broadcasters, and 3) present a model for developing the competence of television news broadcasters. The research design was a mixed method. The research was qualitative, using in-depth interview from 12 key informants. Next, a brainstorming group discussion was held to consider the draft model obtained from 7 experts as well as to confirm the pattern with quantitative research. The quantitative research used simple random sampling and selective selection to make questionnaires for collecting data from 400 the sample group. The statistics for analysis data were percentage, mean and standard deviation. The results showed that the competence of television news broadcasters for television broadcasting in Thailand could be divided into 4 areas: core competencies, job-specific competencies, management competence, and other performances. As for the development model of the competency of television news broadcasters for television broadcasting in Thailand being developed was called “POUND Model”. There were five components: 1) provisions consisted of 2 parts: basic core competencies includes knowledge, skills, physical attributes and equilibrium management competence, 2) appropriateness individual core competencies includes knowledge, skills, physical attributes, and internal drives, 3) utilities includes knowledge, skills, and physical attributes, 4) natural characteristics includes internal driving competencies and physical performance, and 5) divertissement individual core competencies consists of skills and physical attributes. Furthermore, there should be a study of the competence of television news broadcasters having dependance on factors and contexts of the audience, time, technology, social-economic conditions and competition in the industry. Also, study tools or methods for developing competency of television news broadcasters should be reviewed to have similar concrete standards as well.